2024
DOI: 10.7759/cureus.57943
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and Predictive Significance of Serum Leptin Levels in Non-alcoholic Fatty Liver Disease

Mehwish Qamar,
Abeer Fatima,
Ambreen Tauseef
et al.

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) has emerged as the single most common chronic non-viral liver disease. The burden of the disease on healthcare-providing services has increased tremendously. Although a liver biopsy is the most authentic laboratory investigation for scoring the disease progression, it is an invasive technique. Researchers are vigorously working to find alternate markers for the scoring purpose. Despite the importance and association of leptin with metabolic syndrome and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this study, the control group had averages of 20.4 ± 2.5 ng/mL, and those with MASH had levels up to 37.4 ± 9 ng/mL; participants had BMI > 25 kg/m 2 and were mostly female, and even the controls were overweight. Estrogen can increase leptin levels in rats and humans [ 88 ]; females exhibit leptin and insulin resistance rather than sensitization to leptin’s sympathoexcitatory actions [ 40 ], and threshold levels are unknown [ 87 , 89 ]. Hyperleptinemia itself can cause leptin resistance [ 14 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the control group had averages of 20.4 ± 2.5 ng/mL, and those with MASH had levels up to 37.4 ± 9 ng/mL; participants had BMI > 25 kg/m 2 and were mostly female, and even the controls were overweight. Estrogen can increase leptin levels in rats and humans [ 88 ]; females exhibit leptin and insulin resistance rather than sensitization to leptin’s sympathoexcitatory actions [ 40 ], and threshold levels are unknown [ 87 , 89 ]. Hyperleptinemia itself can cause leptin resistance [ 14 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plasma leptin concentration in the cerebral spinal fluid either hits a plateau without change or does not increase when levels rise over 25 to 30 ng/mL [15,86]. Quamar et al found that normal-weight controls had leptin levels of 10 (17.1) ng/mL, while individuals with MASLD had levels of 20.5 (21) ng/mL [87]. In this study, the control group had averages of 20.4 ± 2.5 ng/mL, and those with MASH had levels up to 37.4 ± 9 ng/mL; participants had BMI > 25 kg/m 2 and were mostly female, and even the controls were overweight.…”
Section: Leptin Resistancementioning
confidence: 99%